Fractionation of Lignin with Decreased Heterogeneity: Based on a Detailed Characteristics Study of Sequentially Extracted Softwood Kraft Lignin - Liu Rui; Smeds Annika; Wang Luyao; Pranovich Andrey; Hemming Jarl; Willför Stefan; Zhang Hongbo; Xu Chunlin (American Chemical Society, 2025)
Industrial lignin fractionation is attracting increasing interest due to its enormous potential in the development of high value-added materials. However, the widely reported fractionation approaches are primarily focused on the separation of fractions with a low polydispersity index (PDI). In this study, based on the detailed characteristic examination of carefully sequential-extracted softwood Kraft lignin fractions, a novel method to isolate lignin fraction with decreased heterogeneity (LGF-dh), was established in consideration of impurities, elemental composition, molar mass distribution, carbohydrate content, functional hydroxyl content, and the content of lignin-relevant aromatic units. To characterize the mentioned properties, an elemental analyzer, SEC-MALS, GC-MS, GC-FID, Py/GCMS, P-31-NMR, and HSQC-NMR were used to compare the differences of the sequential lignin fractions that were obtained by methyl tert-butyl ether (MTBE), ethyl acetate (EtOAc), ethanol (EtOH), methanol (MeOH), acetone, and dioxane. Moreover, a practical and feasible three-step extraction process was proposed to separate the low heterogeneity lignin fraction from industrial lignin according to the different solubilities of each fraction in the green cosolvent system of EtOH/water, MeOH/water, and acetone/water. Overall, this work presented a comprehensive study on the properties of softwood lignin as well as proposed a feasible and convenient method to reduce the heterogeneity of lignin, which would promote its valorization.